(untitled) (Fiep Bulletin - online, 2016)
INTRODUCTION: According to Brazil ?s Institute of Geography and Statistics (IBGE) of 2004 Brazil may achieve 31 million of elderly in the year of 2020. The Human development Report (2013) points that brazilians life expectancy is currently about 73 years old, while in Germany, for instance is 92 as life expectancy. OBJECTIVE: The current study has as a general goal to identify the BMI (body mass index) parameters; strenght and dynamic balance in elderly residents of an asylum before starting a program in the city of Toledo – PR. METHODOLOGY: The sample was intentional and not based on probabilistic compound by 9 asylum residents; 6 males and 3 medium age 78,2±2,8 years, who will go through to a localized gymnastic program that takes part of an extension Project in Toledo. The dynamic balance was classified by the test Time up and Go (PODSIADLO E RICHARDSON, 1991) and the strength by manual removal using one dynanometer(BOHANNON et al., 2006).RESULTS: Based on the results the BMI in the elderly was detected as overweight. A slight difference was found between manual removal of both right and left hand. Yet, the most concerning data was the dynamic balance with an average of 16,09 seconds; which may be a concerning value for the assessed group. CONCLUSION: The relevance of the study becomes one important tool for the teachers involved to seek conditions, through maintainance or improvement of the physical capacities of strenght and balance, in order to detect and standardize anthropometrical evaluations techniques.